2009
DOI: 10.1155/2009/103123
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Structural Brain MRI in the Diagnosis of Alzheimer’s Disease

Abstract: Abstract. Dementia is a debilitating and life-altering disease which leads to both memory impairment and decline of normal executive functioning. While causes of dementia are numerous and varied, the leading cause among patients 60 years and older is Alzheimer's disease. The gold standard for Alzheimer's diagnosis remains histological identification of amyloid plaques and neurofibrillary tangles within the medial temporal lobe, more specifically the entorhinal cortex and hippocampus. Although no definitive cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 30 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…are among the earliest sites of pathologic involvement in AD [32]. Neuroimaging studies have repeatedly shown decreased hippocampal and ERC volumes in patients with AD compared with age-matched control subjects [33]. MRI studies of MCI have shown that hippocampal volumes and cortical volumes in the parietal and lateral temporal regions are able to predict the likelihood of progression [34].…”
Section: Neuroimaging Biomarkersmentioning
confidence: 99%
“…are among the earliest sites of pathologic involvement in AD [32]. Neuroimaging studies have repeatedly shown decreased hippocampal and ERC volumes in patients with AD compared with age-matched control subjects [33]. MRI studies of MCI have shown that hippocampal volumes and cortical volumes in the parietal and lateral temporal regions are able to predict the likelihood of progression [34].…”
Section: Neuroimaging Biomarkersmentioning
confidence: 99%
“…49 Manual volumetry of the hippocampus discriminates AD and healthy control groups with high accuracy 50 and displays a multicenter variability of Ͻ5%. 51,52 It is, therefore, considered the best established imaging biomarker of AD to date.…”
Section: Brain Structurementioning
confidence: 99%
“…Structural CT and MRI scans are mainly used to assess volumetric changes in dementias with decreases in gyral and increases in sulcal size secondary to decrease in synaptic density, neuronal loss, and cell shrinkage (Tartaglia et al, 2010). The medial temporal lobes, especially the hippocampus and entorhinal cortex (ERC), are among the earliest sites of pathologic involvement in AD (Braak & Braak, 1991), and studies have repeatedly shown decreased hippocampal and ERC volumes in patients with AD compared with age-matched controls (Appel et al, 2009). Other severely affected areas include the lateral parietal and posterior superior temporal regions and medial posterior portion of the cingulate gyrus (Jones et al, 2006), but atrophy is also evident in the frontal, temporal, and occipital lobes (Rusinek et al, 1991).…”
Section: Functional Neuroimaging In Dementiamentioning
confidence: 99%